2016
DOI: 10.1016/j.jinsphys.2016.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pollen dilution on infection of Nosema ceranae in honey bees

Abstract: Multiple stressors are currently threatening honey bee health, including pests and pathogens. Among honey bee pathogens, Nosema ceranae is a microsporidian found parasitizing the western honey bee (Apis mellifera) relatively recently. Honey bee colonies are fed pollen or protein substitute during pollen dearth to boost colony growth and immunity against pests and pathogens. Here we hypothesize that N. ceranae intensity and prevalence will be low in bees receiving high pollen diets, and that honey bees on high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
70
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(81 citation statements)
references
References 76 publications
11
70
0
Order By: Relevance
“…Therefore, the actual energetic cost of mounting the immune response against the Nosema infection (Huang et al, 2012;Lochmiller & Deerenberg, 2000) might not be relevant in the tolerant honeybees. This is also supported by data showing that better alimentation affected host survival positively regardless the severity of the Nosema infection (Jack et al, 2016).…”
Section: Discussionsupporting
confidence: 58%
“…Therefore, the actual energetic cost of mounting the immune response against the Nosema infection (Huang et al, 2012;Lochmiller & Deerenberg, 2000) might not be relevant in the tolerant honeybees. This is also supported by data showing that better alimentation affected host survival positively regardless the severity of the Nosema infection (Jack et al, 2016).…”
Section: Discussionsupporting
confidence: 58%
“…For example, Plasmodium blood-stage parasites can sense the levels of host nutrient intake and modulate replication and virulence based on nutrient availability (Mancio-Silva et al, 2017). We found that a pollen diet significantly increased the number of N. ceranae spores within the honey bee midgut similar to other studies (Zheng et al, 2014;Fleming et al, 2015;Jack et al, 2016). This suggests a similar host-parasite dynamic may exist between A. mellifera and N. ceranae.…”
Section: Effects Of Parasitic Stress From Nosema Ceranaesupporting
confidence: 82%
“…A). This is consistent with a recent study indicating that N. ceranae may affect hypopharyngeal gland protein synthesis, supporting the assertion that N. ceranae may disrupt protein metabolism in bees (Jack et al ., ). An elevation of peroxide concentration in midguts might indicate the activity of Duox, an NADPH oxidase known to be involved in gut immunity against several pathogens in Drosophila (Lemaitre and Hoffmann, ; Ferrandon, ; Buchon et al ., ).…”
Section: Discussionmentioning
confidence: 97%